Clinical and Laboratory Characteristics and Differential Diagnosis between Secondary Hemophagocytic Syndrome and Sepsis - VG Potapenko; MYu Pervakova; AV Titov; OV Goloshchapov; SV Lapin; EA Surkova; AV Klimovich; OP Mironova; NN Petrova; NYu Chernookaya; EV Karyagina; NV Skorobogatova; et al. (Клиническая онкогематология)

(untitled)
Background. Secondary hemophagocytic syndrome (SHPS) and sepsis, although very similar in their clinical manifestations and laboratory parameters, essentially differ in terms of methods of their treatment. SHPS therapy is aimed at immunosuppression, whereas in sepsis anti-infectious treatment is required. To choose the correct therapy a rapid differential diagnosis is necessary.